Molecular investigation of how drought stress affects chlorophyll metabolism and photosynthesis in leaves of C3 and C4 plant species: A transcriptome meta-analysis - Shima Karami; Behrouz Shiran; Rudabeh Ravash (Heliyon)
Drought stress has a significant impact on photosynthesis in plants, leading to reduced photosynthesis rates and affecting plant growth and yield. Understanding the effects of drought stress on photosynthetic pathways, particularly in C3 and C4 plants, is crucial for maximizing agricultural productivity and maintaining food security. In this study, we analyzed RNA-seq data from leaves of common wheat (Triticum aestivum) and sorghum (Sorghum bicolor), as representatives of C3 and C4, using a meta-analysis approach to investigate the photosynthesis-related genes involved in the response to drought stress. We identified specific genes and components of the photosynthesis pathway that are affected by drought stress. The findings suggest that wheat and sorghum respond differently to drought stress, with sorghum showing a more effective defense system against photoinhibition and damage to photosystems. On the other hand, it seems that in wheat, in order to deal with oxidative stress, the expression of homologous genes of C4 enzyme and genes involved in heme and siroheme synthesis pathway has increased under stress. This is probably due to the higher photoinhibition in C3 photosynthetic system compared to C4. Furthermore, drought stress affected chlorophyll biosynthesis and degradation pathways in both wheat and sorghum, but compared with sorghum, drought stress had a greater inhibitory effect on chlorophyll biosynthesis in wheat, which indicates the difference in their ability to cope with photoinhibition.